The Long-Run Effects of Recessions on Education and Income - Bryan Stuart (Institute of Labor Economics (IZA), 2019)
This paper examines the long-run effects of the 1980-1982 recession on education and income. Using confidential Census data, I estimate difference-in-differences regressions that exploit variation across counties in recession severity and across cohorts in age at the time of the recession. For individuals age 0-10 in 1979, a 10 percent decrease in earnings per capita in their county of birth reduces four-year college degree attainment by 10 percent and income in adulthood by 3 percent. Simple calculations suggest that, in aggregate, the 1980-1982 recession led to 0.8-1.8 million fewer college graduates and 42-87 billion less earned income per year.
Keywords: E32; I20; I30; J13; J24; 330; human capital; education; income; recessions